Loss of olfactory sensitivity is an early and reliable marker for COVID-19. (7th September 2022) - Iravani, Behzad; Arshamian, Artin; Lundström, Johan N
Abstract: Detection of early and reliable symptoms is important in relation to limiting the spread of an infectious disease. For COVID-19, the most specific symptom is either losing or experiencing reduced olfactory functions. Anecdotal evidence suggests that olfactory dysfunction is also one of the earlier symptoms of COVID-19, but objective measures supporting this notion are currently missing. To determine whether olfactory loss is an early sign of COVID-19, we assessed available longitudinal data from a web-based interface enabling individuals to test their sense of smell by rating the intensity of selected household odors. Individuals continuously used the interface to assess their olfactory functions and at each login, in addition to odor ratings, recorded their symptoms and results from potential COVID-19 test. A total of 205 COVID-19-positive individuals and 156 pseudo-randomly matched control individuals lacking positive test provided longitudinal data which enabled us to assess olfactory functions in relation to their test result date. We found that odor intensity ratings started to decline in the COVID-19 group as early as 6 days prior to the test result date (±1.4 days). Symptoms, such as sore throat, aches, and runny nose appear around the same point in time; however, with a lower predictability of a COVID-19 diagnosis. Our results suggest that olfactory sensitivity loss is an early symptom but does not appear before other related COVID-19 symptoms. Olfactory loss is, however, more predictive of a COVID-19 diagnosis than other early symptoms.